Yokohama kaidashi kikou. 3 - Ashinano, Hitoshi (Seven Seas Entertainment, 2023)
"A summer storm passes over the café, reminding Alpha that everything, even her memory, is changing all the time. She takes a tour through the seasons on foot, to record all she can in her memories. The days slide easily into the future"--